Bibliometric analysis of pancreatic cancer liver metastasis research: global trends, collaborations, and emerging research hotspots - Huang, Yingjie; Yin, Zhijie; Han, Wei (Frontiers in Oncology, 2025)
BackgroundPancreatic cancer liver metastasis (PCLM) is a critical condition characterized by the spread of pancreatic cancer to the liver, significantly contributing to cancer-related mortality. The importance of understanding the epidemiology and research trends in PCLM cannot be overstated, as it impacts the development of effective treatment strategies and patient care in oncology.MethodThis study provides a comprehensive epidemiological and bibliometric analysis of PCLM research. Advanced visualization tools such as VOSviewer, CiteSpace, and the R package “bibliometrix” were utilized to analyze the literature. A total of 3,941 publications were identified, covering a 15-year period from 2010 to 2024. The methodology included the identification of publication trends, country and institutional contributions, leading journals, and keyword co-occurrence analysis to uncover research hotspots.ResultsThe annual publication counts exhibited an upward trend, peaking at 384 in 2024, indicating a growing interest in PCLM research. The research included contributions from 90 countries and 4386 institutions, with China and the United States being the most prolific. The journal Cancers was identified as the most frequent publisher in this field. Keyword co-occurrence analysis revealed “cancer” and “pancreatic cancer” as key research hotspots, with a focus on prognostic factors and therapeutic strategies. The study also highlighted the importance of international collaboration and identified key contributors in the field.ConclusionThe findings of this study reveal the significant increase in PCLM research output, emphasizing the need for continued investigation and collaboration to improve treatment outcomes and patient care. While the study is limited by its reliance on bibliometric data without experimental validation, it nonetheless provides valuable insights into publication trends and emerging research themes in PCLM. The results underscore the importance of further research to enhance our understanding of this challenging area of oncology and to guide future research directions.